2022
DOI: 10.1186/s12864-022-08670-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of tuberous root in two sweet potato varieties reveals the important genes and regulatory pathways in tuberous root development

Abstract: Background Tuberous root formation and development is a complex process in sweet potato, which is regulated by multiple genes and environmental factors. However, the regulatory mechanism of tuberous root development is unclear. Results In this study, the transcriptome of fibrous roots (R0) and tuberous roots in three developmental stages (Rl, R2, R3) were analyzed in two sweet potato varieties, GJS-8 and XGH. A total of 22,914 and 24,446 differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
0
12
1
Order By: Relevance
“…sweet potatoes [23], and cassava [24,25]. Subsequently, the weight gain ratio of the tuberous root slowly increased.…”
Section: Discussionmentioning
confidence: 99%
“…sweet potatoes [23], and cassava [24,25]. Subsequently, the weight gain ratio of the tuberous root slowly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of starch biosynthesis and downregulation of lignin biosynthesis in potential storage roots are the main events during the storage root formation period [ 8 , 15 , 22 ], probably because the activity of carbon flow towards carbohydrate metabolism is stronger than the delivery into phenylpropanoid biosynthesis during the storage root formation period [ 14 , 30 ]. Previous findings have shown that low sucrose and high hexose content in the root system could facilitate storage root formation [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ibkn1, Ibkn2, and Ibkn3 are members of the class I knotted 1-like (KNOX-box) gene family, and they are expressed in primary cambium cells [ 8 , 15 ]. They regulate cell proliferation and differentiation in potential storage roots [ 22 , 23 ], and their expression in storage roots was two-fold higher than that in fiber roots [ 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through transcriptome analysis, researchers discovered that the expression of potato genes varies greatly among different varieties [32], which directly affects individual differ-ences in potato growth. Among cultivars, there are significant variations in the expression profiles of genes that affect tuber development [33]. The variation in gene expression is more prominent in potatoes with high heterozygosity and tetraploid inbreeding inhibition [34].…”
Section: Rna-seq Screened 85 Cadmium Tolerance Genes In Potatomentioning
confidence: 99%